2017
DOI: 10.1099/ijsem.0.002256
|View full text |Cite
|
Sign up to set email alerts
|

Proposal to correct the generic name Flaviaesturariibacter Kang, Chun, Seo, Kim and Jahng 2015, 2212 to Flavaestuariibacter. Request for an Opinion

Abstract: The generic name Flaviaesturariibacter Kang, Chun, Seo, Kim and Jahng 2015, 2212 is malformed: being derived from the Latin noun aestuarium, …aestuarii… instead of …aesturarii… is required. Moreover, according to Appendix 9 of the Prokaryotic Code, a connecting vowel must be dropped when the following word element starts with a vowel. I therefore propose to correct the name Flaviaesturariibacter to Flavaestuariibacter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A Request for an Opinion by Oren [65] called for the orthographical correction of the name Flaviaesturariibacter Kang et al . 2015 to Flavaestuariibacter .…”
Section: Opinion 118mentioning
confidence: 99%
See 2 more Smart Citations
“…A Request for an Opinion by Oren [65] called for the orthographical correction of the name Flaviaesturariibacter Kang et al . 2015 to Flavaestuariibacter .…”
Section: Opinion 118mentioning
confidence: 99%
“…This indicates that the intended spelling was Flaviaestuariibacter derived from the Latin neuter noun aestuarium , which can, in contrast to aesturarium , be found in dictionaries, as stated by Oren [65]. However, the Judicial Commission could not confirm the claim in the Request for an Opinion [65] that the Notification List that included the name [67] already corrected the spelling to Flaviaestuariibacter ; instead it also used Flaviaesturariibacter .…”
Section: Opinion 118mentioning
confidence: 99%
See 1 more Smart Citation
“…Some Requests for an Opinion directly proposed orthographical corrections of names [7, 8]. M. Göker suggested that the orthographical corrections to be conducted should be carefully chosen.…”
Section: Minute 4 Debate Of the Current Drafts For Judicial Opinionsmentioning
confidence: 99%
“…The ballot was intended to be held in the weeks directly after the video conference. A variety of Requests for an Opinion were under consideration [1–11].…”
Section: Minute 4 Debate Of the Current Drafts For Judicial Opinionsmentioning
confidence: 99%